MINAT BACA DAN GAYA BELAJAR MAHASISWA LPTK SEBAGAI CALON GURU PROFESIONAL DI ERA DIGITAL - Anna Armeini Rangkuti, Lussy Dwiutami Wahyuni, Winda Dewi Listyasari (Perspektif Ilmu Pendidikan, 2017)
The purpose of conducting this research was to examine whether there is significant correlation or not between reading interest and learning style of LPTKâ€™s students as professional teacher candidates. 126 samples were taken from 4 LPTK was previously a state Teachersâ€™ Training College (IKIP Negeri) in June - November 2016, involving 126 respondents. Data were analyzed using an application aid Statistical Product and Service Solutions (SPSS) version 21 and Winstep version 37.1 applications Rasch modeling to determine the categories of respondents are more uncertain. Hypotheses were tested using Cramerâ€™s V nonparametric correlation method. The Result showed that approximate significantly. (0.818) was higher that alpha (0.05), it can be concluded that the Null Hypothesis (H0) â€œthere is no significant correlation between reading interest and learning style on LPTKâ€™s studentsâ€.